Kerangka komprehensif pemikiran Melayu abad ke-17 masihi berdasarkan manuskrip Durr al-Fara’id karangan Sheikh Nurudin al-Raniri - Wan Mohd Nor Wan Daud,; Khalif Muammar, (Universiti Kebangsaan Malaysia, 2009)
This paper examines arguably the first and one of the most important writings of al-Raniri and yet received little attention by scholars of the Malay world to date. After the manuscripts from Jakarta, Aceh and Kuala Lumpur are discovered and studied, the present authors find out that Durr al-Fara’id bi Sharh al- Aqa’id is the first work of al-Raniri, and the one which elevated him to the position of a respected theologian and grand scholar of his time. This work was completed by al-Raniri in 1040 Hijri (1630 C.E.), few years before he was appointed as the chief Mufti of the Kingdom of Aceh Darussalam. This study finds that the work was circulated widely in the Malay world and copied by copyists from different generations. The work is undeniably needed to be studied and re-introduced since it discusses early Muslim theology, particularly the Sunni creed which includes epistemology, ontology, shari’ah and politics. Although it is basically a translation work, al-Raniri contribute roughly 50% of his own ideas and make it suitable for the context of the Malay world. Since it is based on a great book, i.e. ‘Aqa’id al-Nasafi, the fundamental and critical matters discussed in this work make it a great work by its own which potrays the worldview of Muslims in the Malay world during the 17th Century and afterward